PERAN STAKEHOLDER DALAM MENGATASI KETIMPANGAN PENDIDIKAN DI DAERAH TERPENCIL : TANTANGAN DAN SOLUSI - Sari, Fitria; Erwin Salpa Riansi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education is an important pillar in a country's development, but educational inequality in remote areas of Indonesia is a serious challenge. This article explores the role of stakeholders-the government, educational institutions, communities and the private sector-in addressing these inequalities. Stakeholders have a responsibility to improve access and quality of education, especially in isolated areas. The government plays a role in formulating policies and providing education infrastructure, while education institutions are required to adapt the curriculum to be relevant to local needs. Community organizations and NGOs serve as a bridge between the government and the community, providing non-formal education and identifying specific challenges. The private sector, through corporate social responsibility (CSR) programs, can provide financial support and construction of education facilities. The article also discusses the challenges faced, including limited infrastructure, a shortage of qualified teaching staff, and social and economic issues that hinder educational participation. Various solutions are proposed, such as increasing scholarships, providing transportation, and using technology in education. Through collaboration between all stakeholders, it is hoped that access to and quality of education in remote areas can improve, creating more equitable opportunities for all children. This conclusion emphasizes the importance of integrated efforts in addressing education inequality to support sustainable development in Indonesia.